Protein fiber-based composite aerogel material and preparation method thereof

By combining vegetable-tanned leather fibers and photothermal conversion particles, the photothermal conversion performance and structural stability of aerogel materials are improved, and the problem of low efficiency of traditional aerogel materials when adsorbing high viscosity oil stains is solved. , achieving efficient and stable adsorption effect.

CN119236888AActive Publication Date: 2025-01-03嘉兴南湖学院 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411666248.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-03
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Traditional aerogel materials tend to clog pores when adsorbing high viscosity oil stains, resulting in low adsorption efficiency and difficult to recover.

Method used

Vegetable tanned leather fibers are used as raw materials for protein fiber-based composite aerogels, and the photothermal conversion performance of its tannins is used to reduce the amount of photothermal conversion particles, improve the photothermal conversion performance of aerogel materials, and through specific preparation The method forms a stable three-dimensional structure to enhance the adsorption ability to high viscosity oil stains.

Benefits of technology

It improves the efficient and stable adsorption performance of aerogel materials on high viscosity oil stains, avoids the damage to three-dimensional structure caused by excessive photothermal conversion particles, and enhances the physical properties and adsorption capabilities of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236888A_ABST
    Figure CN119236888A_ABST
Patent Text Reader

Abstract

The invention discloses a protein fiber-based composite aerogel material and a preparation method thereof, and relates to the technical field of adsorption materials. According to the protein fiber-based composite aerogel material and the preparation method thereof provided by the invention, the vegetable leather fiber is adopted as a protein fiber-based raw material of the protein fiber-based composite aerogel, so that the photo-thermal conversion performance of tannin in the vegetable leather fiber component can be fully utilized, and the dosage of photo-thermal conversion particles in the preparation process of the aerogel material is reduced; therefore, the photo-thermal conversion performance of the aerogel material is improved, meanwhile, the technical problem that a three-dimensional structure is damaged due to the fact that the using amount of the photo-thermal conversion particles is too large is solved, and then the efficient and stable adsorption performance of the aerogel material to high-viscosity oil stains is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to a protein fiber-based composite aerogel material and a preparation method thereof. Background Art

[0002] As a typical adsorbent material, aerogel has a highly porous structure and a large surface area that can accommodate a large amount of liquid and has excellent oil absorption performance. At the same time, the low density of aerogel allows it to easily float on the water surface after absorbing oil, which facilitates the recycling and reuse of oil, making aerogel an ideal choice for treating oil pollution, oil leaks and other liquid pollution.

[0003] The oil absorption principle of traditional aerogel materials is mainly physical adsorption. The oil-water contact angle on the surface of aerogel materials is relatively small, and there is a certain tension at the oil-water interface. When it comes into contact with oil, the tension gathers the oil into the microchannels of the pores of the aerogel material and is adsorbed by hollow capillaries and macroporous polymers to form a certain thickness.

[0004] In the process of using the aerogel material provided by the related technology to perform oil pollution adsorption operations, the inventors found that the related technology has the following technical problems:

[0005] When the aerogel material provided by the related technology is applied to the adsorption scenario of oil pollution, if the viscosity of the oil pollution to be adsorbed is relatively large, for example, the viscosity of petroleum is 103~105mPa·s at room temperature, then the viscous oil pollution can easily clog the pores of the aerogel material and cannot be effectively adsorbed, resulting in poor adsorption efficiency of the aerogel material for oil pollution and difficulty in recovery. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the present invention provides a protein fiber-based composite aerogel material and a preparation method thereof. By using vegetable tanned leather fiber as the protein fiber-based raw material of the protein fiber-based composite aerogel, the photothermal conversion performance of tannin in the vegetable tanned leather fiber component can be fully utilized, and the amount of photothermal conversion particles used in the preparation process of the aerogel material can be reduced, thereby achieving the goal of improving the photothermal conversion performance of the aerogel material while avoiding the technical problem of three-dimensional structure damage caused by excessive use of photothermal conversion particles, thereby improving the efficient and stable adsorption performance of the aerogel material for high-viscosity oil stains. The technical solution provided by the present invention is as follows:

[0007] According to a first aspect of an embodiment of the present invention, a method for preparing a protein fiber-based composite aerogel material is provided, wherein the method comprises:

[0008] S10: adding the vegetable tanned leather fiber to the dimethyl sulfoxide solvent, and keeping the mixture in an environment of 80° C. for 30 minutes until the fiber is completely dissolved, thereby obtaining a vegetable tanned leather fiber / dimethyl sulfoxide solution, wherein the content of the vegetable tanned leather fiber in the vegetable tanned leather fiber / dimethyl sulfoxide solution is 5 g / 100 ml;

[0009] S20: After adding chitosan powder to distilled water, continue to slowly drop glacial acetic acid until the chitosan powder is completely dissolved to obtain a first mixed solution, and then adjust the pH of the first mixed solution to 4 to obtain a chitosan solution, wherein the content of the chitosan powder in the chitosan solution is 4 g / 100 ml, and the volume ratio of the glacial acetic acid to the distilled water is 1:1;

[0010] S30: mixing the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in a volume ratio of 1-2:1-2:1-2, adding C-NPs with stirring and evenly dispersing to obtain a second mixed solution, and then dispensing the second mixed solution into each porous plate, adding glutaraldehyde solution to the second mixed solution in each porous plate, stirring and sealing, and keeping warm at 60° C. for 4 hours to obtain a composite wet gel semi-finished product, wherein the mass of the C-NPs is 0.15% of the mass of the vegetable tanned leather fiber;

[0011] S40: taking out the composite wet gel semi-finished product from each porous plate and placing it at room temperature for 12-36 hours, soaking the composite wet gel semi-finished product in anhydrous ethanol for 12-36 hours, taking it out, and then soaking the composite wet gel semi-finished product in ultrapure water for another 12-36 hours to obtain a carbon nano-protein-based composite wet gel material;

[0012] S50: placing the carbon nano-protein-based composite wet gel material in a -60°C environment for freeze-forming, and then sending it into a vacuum freeze dryer for freeze-drying to obtain a carbon nano-protein-based composite aerogel;

[0013] S60: After the carbon nano-protein-based composite aerogel is immersed in a PDMS hydrophobic agent solution for modification for 2 hours, it is placed in a 120° C. environment for drying for 20 minutes to obtain a protein fiber-based composite aerogel material.

[0014] Preferably, the volume ratio of the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in S30 is 2:2:4.

[0015] Preferably, the content of glutaraldehyde in the glutaraldehyde solution is 2.5%, and the volume ratio of the glutaraldehyde solution to the vegetable tanned leather fiber / dimethyl sulfoxide solution in each porous plate is 3:50.

[0016] Preferably, the composite wet gel semi-finished product is allowed to stand at room temperature for 24 hours, is immersed in anhydrous ethanol for 12 hours, and is immersed in ultrapure water for 12 hours.

[0017] Preferably, the content of PDMS in the PDMS hydrophobic agent solution is 1.5%.

[0018] Preferably, the method for preparing the vegetable tanned leather fiber comprises:

[0019] The vegetable tanned leather scraps were cut into 2 cm × 3 cm sizes and then put into a grinder for grinding for 5 min to obtain the vegetable tanned leather fiber raw materials;

[0020] The vegetable tanned leather fiber raw material is soaked in anhydrous ethanol for 2-4 days to wash out alcohol-soluble impurities, and then filtered and dried at 120° C. for 2 hours, and finally sent to a grinder for grinding for 5 minutes to obtain the vegetable tanned leather fiber.

[0021] Preferably, the protein fiber-based composite aerogel material is used in petroleum adsorption operations.

[0022] According to a second aspect of an embodiment of the present invention, a protein fiber-based composite aerogel material is provided, characterized in that the protein fiber-based composite aerogel material is prepared by the method for preparing the protein fiber-based composite aerogel material described in any one of 1 above.

[0023] Compared with the prior art, the protein fiber-based composite aerogel material and the preparation method thereof provided by the present invention have the following advantages:

[0024] The invention provides a protein fiber-based composite aerogel material and a preparation method thereof. The preparation method comprises: adding vegetable tanned leather fiber to a dimethyl sulfoxide solvent, and keeping the mixture in an environment of 80°C for 30 minutes until the mixture is completely dissolved, thereby obtaining a vegetable tanned leather fiber / dimethyl sulfoxide solution; adding chitosan powder to distilled water, and then slowly dripping glacial acetic acid until the chitosan powder is completely dissolved, thereby obtaining a first mixed solution; and adjusting the pH value of the first mixed solution to 4 to obtain a chitosan solution; mixing the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in a volume ratio of 1-2:1-2:1-2, and then stirring and adding C-NPs and dispersing the mixture uniformly to obtain a second mixed solution; and then dispensing the second mixed solution into each porous plate, and then adding a glutaraldehyde solution into the second mixed solution in each porous plate, and then stirring and sealing the mixture; and keeping the mixture in an environment of 60°C for 4 minutes. h to obtain a composite wet gel semi-finished product, wherein the mass of C-NPs is 0.15% of the mass of the vegetable tanned leather fiber; the composite wet gel semi-finished product is taken out from each porous plate and placed at room temperature for 12-36 hours, and then the composite wet gel semi-finished product is soaked in anhydrous ethanol for 12-36 hours and then taken out, and then the composite wet gel semi-finished product is soaked in ultrapure water for 12-36 hours to obtain a carbon nano-protein-based composite wet gel material; the carbon nano-protein-based composite wet gel material is placed in a -60°C environment for freeze-forming, and then sent to a vacuum freeze dryer for freeze-drying to obtain a carbon nano-protein-based composite aerogel; the carbon nano-protein-based composite aerogel is soaked and modified with a PDMS hydrophobic agent solution for 2 hours, and then placed in a 120°C environment for drying for 20 minutes to obtain a protein fiber-based composite aerogel material. The present invention utilizes the photothermal conversion performance of tannin in the vegetable tanned leather fiber component to reduce the amount of photothermal conversion particles used in the preparation process of aerogel materials, thereby improving the photothermal conversion performance of the aerogel material while avoiding the problem of three-dimensional structure damage caused by excessive use of photothermal conversion particles, thereby improving the efficient and stable adsorption performance of the aerogel material for high-viscosity oil stains. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0026] Figure 1 The present invention is a flowchart showing a method for preparing a protein fiber-based composite aerogel material according to an exemplary embodiment of the present invention.

[0027] Figure 2 It is a schematic diagram of preparing a vegetable tanned leather fiber according to an exemplary embodiment of the present invention.

[0028] Figure 3 1 is a scanning electron microscope image of four aerogels shown in the present invention.

[0029] Figure 4It is a schematic diagram of the test results of the resilience performance of the aerogel shown in the present invention.

[0030] Figure 5 It is a schematic diagram of the adsorption rate of three oils by PDMS@C-PCA provided by the present invention at room temperature.

[0031] Figure 6 It is a schematic diagram of the photothermal performance analysis experiment of the aerogel shown in the present invention.

[0032] Figure 7 It is a schematic diagram of the temperature change of the aerogel under a simulated light source shown in the present invention.

[0033] Figure 8 It is a schematic diagram of an ultrasonic stability analysis experiment of aerogel shown in the present invention. DETAILED DESCRIPTION

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] In order to facilitate the understanding of the technical solution provided by the present invention, before specifically describing the preparation method of a protein fiber-based composite aerogel material provided by the present invention, the following terms involved in the specific implementation methods of the present invention are explained as follows:

[0036] Photothermal conversion: refers to the phenomenon of photoinduced heating, usually refers to the material heating up when exposed to light. There are three main photothermal conversion mechanisms: plasma interface vibration, non-radiative relaxation, and molecular thermal vibration.

[0037] Photothermal conversion particles: According to the above photothermal conversion mechanism, they are divided into the following three categories:

[0038] 1) Particles that absorb photons through electron transitions and achieve photothermal conversion by resonant heating, such as Au, AG, Pd, Pt, Al, etc.

[0039] 2) After being exposed to light, electron-hole pairs are generated, thereby relaxing radiation energy and causing heat generation in semiconductor particles;

[0040] 3) Particles that absorb sunlight energy and generate heat through electron transitions, mainly black carbon-based materials such as graphene, carbon nanotubes, carbon dots, etc., use π-π conjugated bonds to convert the absorbed energy into heat energy. The C-NPs used in the present invention are such photothermal conversion particles.

[0041] Photothermal oil absorption: A technology that uses solar energy to absorb and decompose oil pollution. Since crude oil is very viscous at room temperature, the adsorbent material needs to increase the temperature of the crude oil to reduce its viscosity and increase its fluidity to facilitate adsorption and improve adsorption efficiency. The adsorbent material with photothermal properties quickly heats up on the upper surface under the sun, and the temperature of the lower surface rises through heat conduction. The lower surface is in direct contact with the oil, so that the viscosity of the oil can be reduced after heating, and the adsorbent can work smoothly, thereby improving the oil absorption efficiency and realizing the treatment and recovery of oil pollution.

[0042] Figure 1 is a method flow chart of a method for preparing a protein fiber-based composite aerogel material according to an exemplary embodiment of the present invention. Figure 1 As shown, the preparation method of the protein fiber-based composite aerogel material is characterized in that the preparation method comprises:

[0043] S10: After adding the vegetable tanned leather fiber to the dimethyl sulfoxide solvent, the mixture is kept at 80° C. for 30 minutes until the fiber is completely dissolved, thereby obtaining a vegetable tanned leather fiber / dimethyl sulfoxide solution, wherein the content of the vegetable tanned leather fiber in the vegetable tanned leather fiber / dimethyl sulfoxide solution is 5 g / 100 ml.

[0044] Preferably, the method for preparing the vegetable tanned leather fiber comprises:

[0045] The vegetable tanned leather scraps are cut into 2cm×3cm sizes, and then sent to a grinder for grinding for 5 minutes to obtain vegetable tanned leather fiber raw materials; the vegetable tanned leather fiber raw materials are soaked in anhydrous ethanol for 2-4 days to wash out alcohol-soluble impurities, and then filtered and dried at 120°C for 2 hours, and finally sent to a grinder for grinding for 5 minutes to obtain vegetable tanned leather fibers.

[0046] The schematic diagram of the preparation of vegetable tanned leather fiber can be shown as follows Figure 2 As shown, the preparation order is Figure 2 1A, 1B, 1C, 1D, 1E.

[0047] S20: After adding the chitosan powder to the distilled water, continue to slowly drop glacial acetic acid until the chitosan powder is completely dissolved to obtain a first mixed solution, and then adjust the pH of the first mixed solution to 4 to obtain a chitosan solution, wherein the content of the chitosan powder in the chitosan solution is 4 g / 100 ml, and the volume ratio of the glacial acetic acid to the distilled water is 1:1.

[0048] S30: After mixing the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in a volume ratio of 1-2:1-2:1-2, stirring and adding C-NPs and dispersing evenly to obtain a second mixed solution, and then packaging the second mixed solution into each porous plate, adding glutaraldehyde solution to the second mixed solution in each porous plate, stirring evenly and then sealing, and keeping warm at 60°C for 4h to obtain a composite wet gel semi-finished product, wherein the mass of the C-NPs is 0.15% of the mass of the vegetable tanned leather fiber.

[0049] S40: After taking out the composite wet gel semi-finished product from each porous plate and placing it at room temperature for 12-36 hours, soaking the composite wet gel semi-finished product in anhydrous ethanol for 12-36 hours and then taking it out, and then soaking the composite wet gel semi-finished product in ultrapure water for another 12-36 hours to obtain a carbon nano-protein-based composite wet gel material.

[0050] Among them, the step of taking out the composite wet gel semi-finished product from each porous plate and placing it at room temperature for 12-36 hours allows the sol inside the composite wet gel semi-finished product to fully age the gel under the cross-linking action of glutaraldehyde; the step of taking out the composite wet gel semi-finished product after soaking it in anhydrous ethanol for 12-36 hours allows the fillers in the wet gel network of the composite wet gel semi-finished product, mainly DMSO, residual glutaraldehyde, etc. in the reaction, to be fully replaced; the step of continuing to soak the composite wet gel semi-finished product in ultrapure water for 12-36 hours is for the purpose of facilitating its subsequent freeze-drying molding process.

[0051] S50: placing the carbon nano-protein-based composite wet gel material in a -60°C environment to freeze-form it, and then sending it into a vacuum freeze dryer for freeze drying to obtain a carbon nano-protein-based composite aerogel.

[0052] Through the processing of the above step S50, the solvent liquid in the carbon nano-protein-based composite wet gel material freezes and solidifies the internal solvent at low temperature, and the internal solvent is directly sublimated from the solid state to obtain aerogel by reduced pressure drying under vacuum conditions. Under this condition, the liquid is replaced by ultrapure water or anhydrous ethanol, and then removed by sublimation, and the solid support structure in the gel can be kept intact through the drying process, thereby forming a high porosity, low density aerogel.

[0053] S60: After the carbon nano-protein-based composite aerogel is immersed in a PDMS hydrophobic agent solution for modification for 2 hours, it is placed in a 120° C. environment for drying for 20 minutes to obtain a protein fiber-based composite aerogel material.

[0054] It should be noted that the effect of the amount of photothermal conversion particles on aerogel molding is mainly the stability of its internal three-dimensional network structure. In order to make the aerogel material have better photothermal conversion performance to meet the aerogel material's adsorption requirements for oils, the preparation process of aerogel materials provided by related technologies often requires the use of a large amount of photothermal conversion particles, which can easily lead to a large amount of photothermal conversion particles on the surface of the three-dimensional structure of the prepared aerogel material, thereby reducing the cross-linking effect of the cross-linking agent, and further making the three-dimensional network structure of the prepared aerogel material unable to maintain a long-term stable state after vacuum drying treatment, and the physical resistance is poor, and it cannot be applied to the actual long-term stable operation of marine oil pollution adsorption.

[0055] Vegetable tanned leather is tanned mainly with vegetable tanning agents. Vegetable tanning agents mainly use vegetable tanning materials and vegetable tannins. Vegetable tannins are polyphenolic compounds such as tannins and plant polyphenols contained in plants that can turn raw hides into leather. The present invention uses vegetable tanned leather fiber as a raw material for preparing carbon nano-protein-based composite aerogel, utilizes a large number of π-π conjugated bonds contained in the hydrolyzed acid of tannin, a component of the fiber, to cause mutual influence of electron clouds, absorb solar energy and vibrate, and generate heat energy through the optical transition of the π-π bonds to enable the aerogel material to have a certain initial photothermal conversion performance, and then through a small amount of doping with photothermal conversion particles C-NPs and the design of the corresponding process flow, the photothermal conversion performance of the prepared carbon nano-protein-based composite aerogel meets the use requirements of its application in photothermal oil absorption, while avoiding the problems of unstable three-dimensional network structure and poor physical properties of the aerogel material caused by doping with a large number of photothermal conversion particles, and the doping of an appropriate amount of C-NPs can also increase the roughness of the surface of the aerogel material, and the rough surface layer and the microporous structure both increase the specific surface area of ​​the aerogel material, which is more conducive to the adsorption and storage of oil products.

[0056] Preferably, the volume ratio of the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in S30 is 2:2:4.

[0057] Preferably, the content of glutaraldehyde in the glutaraldehyde solution is 2.5%, and the volume ratio of the glutaraldehyde solution to the vegetable tanned leather fiber / dimethyl sulfoxide solution in each porous plate is 3:50.

[0058] Preferably, the composite wet gel semi-finished product is allowed to stand at room temperature for 24 hours, is immersed in anhydrous ethanol for 12 hours, and is immersed in ultrapure water for 12 hours.

[0059] Preferably, the content of PDMS in the PDMS hydrophobic agent solution is 1.5%.

[0060] Preferably, the protein fiber-based composite aerogel material is used in petroleum adsorption operations.

[0061] In order to better illustrate the technical effects of the protein fiber-based composite aerogel material and the preparation method thereof provided by the present invention, the following experimental tests were performed on the protein fiber-based composite aerogel material provided by the present invention. For ease of reading, the English abbreviations of the reagents correspond to the following:

[0062] Vegetable tanned leather fiber: VTLF, Vegetable Tanned Leather Fiber;

[0063] Dimethyl sulfoxide: DMSO;

[0064] Chitosan: CS;

[0065] Carbon nano-protein-based composite aerogel: C-PCA, C-NPs-Protein-based Composite Aerogel;

[0066] Protein fiber-based composite aerogel: PDMS@C-PCA.

[0067] The reagents and materials used in the experiment are shown in Table 1. Most of the reagents were analytically pure and chemically pure.

[0068] Table 1

[0069]

[0070]

[0071] Benchmark Experiment Example

[0072] S10: After cutting 10 g of vegetable tanned leather scraps into a size of 2 cm×3 cm, the raw material is put into a grinder and ground for 5 minutes to obtain a vegetable tanned leather fiber raw material; the vegetable tanned leather fiber raw material is soaked in anhydrous ethanol for 2 days to wash out alcohol-soluble impurities, and then filtered and dried at 120° C. for 2 hours, and finally put into a grinder and ground for 5 minutes to obtain VTLF.

[0073] S20: After adding 5 g of VTLF to 100 ml of DMSO solvent, the mixture was kept at 80° C. for 30 min until it was completely dissolved, to obtain a VTLF / DMSO solution.

[0074] S30: After adding 4 g of CS powder to 100 ml of distilled water, 100 ml of glacial acetic acid is slowly added dropwise until the CS powder is completely dissolved to obtain a first mixed solution, and then the pH of the first mixed solution is adjusted to 4 to obtain a CS solution.

[0075] S40: After mixing VTLF / DMSO solution, CS solution and distilled water in a volume ratio of 2:2:4, C-NPs are added with stirring and dispersed evenly to obtain a second mixed solution, and then the second mixed solution is dispensed into each porous plate, and a 2.5% glutaraldehyde solution is added to the second mixed solution in each porous plate, stirred evenly and sealed, and kept warm at 60°C for 4h to obtain a composite wet gel semi-finished product, wherein the mass of the C-NPs is 0.15% of the mass of the VTLF.

[0076] S50: The composite wet gel semi-finished product is taken out from each porous plate and placed at room temperature for 12 hours, and then the composite wet gel semi-finished product is soaked in anhydrous ethanol for 12 hours and then taken out, and then the composite wet gel semi-finished product is soaked in ultrapure water for another 12 hours to obtain a carbon nano-protein-based composite wet gel material.

[0077] S60: The carbon nano-protein-based composite wet gel material is placed in a -60°C environment for freeze-forming, and then sent to a vacuum freeze dryer for freeze-drying to obtain C-PCA.

[0078] S70: After the C-PCA is immersed in a 1.5% PDMS hydrophobic agent solution for modification for 2 hours, it is placed in a 120° C. environment for drying for 20 minutes to obtain PDMS@C-PCA.

[0079] On the basis of the above-mentioned benchmark experimental example, the dosage of VTFL / DMSO was set to 20 ml for experimental testing and optimization, and the chitosan ratio, glutaraldehyde dosage, C-NPs content, aging and water change time were used as influencing factors, and the molding effect of the synthesized aerogel was used as the inspection index for optimization and adjustment. The four factors were independently subjected to single factor experimental design, and each single factor optimization result was directly used in the next single factor experimental design, as follows:

[0080] (1) Experiment on the effect of chitosan ratio on wet gel forming properties

[0081] The effect of chitosan on the formability of aerogel is reflected in the forming effect of wet gel and is determined by subjective evaluation. The role of adding chitosan to assist in forming is that the reaction between chitosan and glutaraldehyde is relatively stable. Adding water is necessary for hydrogel forming on the one hand, and on the other hand, it is to reduce the solid content in the formed aerogel and reduce the density. When the amount of chitosan is too small and more water is added, the mechanical properties of the wet gel may be insufficient. When too much water is added, the forming is general and may affect the subsequent reaction rate. As shown in the optimization results of the chitosan ratio test in Table 2 below, the optimal ratio scheme is determined to be 2:2:4 (V:V:V).

[0082] Table 2

[0083] Test No. VTFL / DMSO:CS:H2O(V:V:V) Molding effect 1 2:2:2 Poor molding, broken 2 2:2:3 General molding 3 2:2:4 Complete molding 4 2:2:5 Poor molding and insufficient mechanical properties 5 2:1;2 General molding 6 2:1:3 Incomplete molding 7 2:1:4 Incomplete molding, broken 8 2:1:5 Poor molding

[0084] (2) Experimental study on the effect of glutaraldehyde dosage on aerogel formability

[0085] The optimal amount of glutaraldehyde was selected based on the aerogel formability, and the results are shown in Table 3. The optimal amount of glutaraldehyde under the optimal ratio of 2:2:4 in (1) was 1.2 ml. A small amount of glutaraldehyde leads to incomplete reaction in the system, affecting the formability; an excessive amount of glutaraldehyde leads to uneven reaction in the porous plate, and the surface cracks due to excessive surface tension caused by the increased reaction rate at 60°C, resulting in poor forming; or it leads to a strong reaction of glutaraldehyde, destroying the three-dimensional structure, and causing collapse after drying.

[0086] Table 3

[0087]

[0088]

[0089] (3) Experiment on the effect of C-NPs dosage on aerogel formability

[0090] The results of the optimization of the amount of C-NPs on aerogels are shown in Table 4. The effect of the amount of C-NPs on aerogel molding is mainly to affect the internal three-dimensional network structure. When the amount of C-NPs is large, the surface load of the three-dimensional structure is large, and the cross-linking effect of glutaraldehyde is weakened, so that the three-dimensional network has insufficient support after vacuum drying, resulting in more serious morphological fragmentation into powder. Therefore, in the scheme (2), the optimal molding content of C-NPs is 0.15%.

[0091] Table 4

[0092] serial number C-NPs dosage / %(VTLF) Forming effect after drying 1 3 Broken, shapeless 2 2 Poor molding, broken 3 1.5 General molding, some breakage 4 1 Incomplete molding 5 0.15 More complete molding

[0093] (4) Experiment on the effect of static aging and water change time on the formability of wet gel and aerogel

[0094] The optimal results of the test on the effects of static aging and water changing time on the formability of wet gel and aerogel are shown in Table 5. Insufficient static aging time will lead to incomplete glutaraldehyde reaction, incomplete wet gel forming, and no porosity and elasticity in the unformed part after drying. Insufficient water changing time will cause the solvent DMSO and some unreacted glutaraldehyde to remain in the reaction system, affecting the porosity. Excessive water changing time will cause the wet gel to swell, the internal three-dimensional structure will be destroyed, and it will collapse severely after drying. On the whole, the optimal solution is static aging and water changing time of 24h each.

[0095] Table 5

[0096]

[0097]

[0098] Based on the optimization results of the above four single-factor experiments, the optimal preparation process of C-PCA is: VTFL / DMSO: CS: H2O (V: V: V) 2:2:4; glutaraldehyde dosage is 1.2 ml; C-NPs content is 0.15%, and after keeping warm for 4 hours, the static aging and water change time are 24 hours each.

[0099] Furthermore, the PDMS@C-PCA corresponding to the C-PCA prepared under the above optimal preparation process was subjected to structural characterization and performance testing, and the data results were obtained as follows:

[0100] Microscopic morphology observation of aerogel

[0101] A small piece of aerogel material was taken from the inside of chitosan aerogel (CA), protein-based composite aerogel (PCA), PDMS@PCA, and PDMS@C-PCA, and then cut, dried, fixed, and gold-sprayed. Then, a field emission scanning electron microscope was used to observe the surface morphology of the material at a working voltage of 15kV, and the surface structure of each sample was analyzed with a parameter of 1000 times. The results are as follows Figure 3 SEM images of the four aerogels shown. Figure 3 As can be seen from (a), the interior of chitosan aerogel (CA) is mainly composed of lamellar pores. Figure 3 The disordered pore cross-distribution structure inside the protein-based composite aerogel (PCA) in (b) is more conducive to the adsorption of oil. Figure 3 In (c), the PDMS hydrophobic layer on the surface of PDMS@PCA is relatively smooth, and PDMS is coated on the surface more evenly, indicating that the hydrophobic modification is relatively successful. Figure 3 Although the surface of PDMS@C-PCA in (d) has a hydrophobic layer, it is a rough surface with uneven spots, which indicates that the dispersion of C-NPs is relatively uniform. In addition, there are many micropores in the cross section. The rough surface and micropore structure increase the specific surface area of ​​the material, which is more conducive to the adsorption and storage of oil products. Therefore, PDMS@C-PCA has better oil absorption capacity. According to actual measurements, the density of PDMS@C-PCA can reach 20mg / cm 3 .

[0102] Aerogel resilience performance test

[0103] Aerogel materials are mainly subjected to a compression-adsorption cycle when reused, so the quality of the material's rebound performance has a direct impact on reusability, so there are certain requirements for the material's rebound performance. The prepared aerogel was subjected to a compression rebound test. The sample was deformed under a fixed compression force (200g weight), and then the weight was released to observe whether the sample recovered to its original state and the degree of recovery. The test was repeated 20 times, and the rebound height and rebound time were recorded to evaluate its compression rebound performance. The rebound performance test results of aerogel are shown in Figure 2. Figure 4 As shown, in Figure 4 In the figure, a is a schematic diagram of the rebound performance corresponding to chitosan aerogel, b is a schematic diagram of the rebound performance corresponding to C-PCA aerogel; c is a schematic diagram of the rebound performance corresponding to PDMS@C-PCA aerogel.

[0104] Depend on Figure 4 It can be seen that when a weight of 200g is placed on the three aerogels and the weight is removed after complete compression without change, the chitosan aerogel has almost no deformation and does not have compression resilience; C-PCA has a small deformation and recovers completely after 10S, and its compression resilience performance is relatively general; while PDMS@C-PCA has a large deformation and can recover quickly within 2S after the pressure is removed, and the recovery rate is almost 100%. During the compression stage, even if the deformation rate is 80%, PDMS@C-PCA does not break or collapse, and its elastic recovery rate is almost 100%, showing excellent resilience. Importantly, even after 20 compression-release cycles, the elastic recovery rate remains at a high level of 92.8%, but the time required for recovery is extended. This shows that PDMS@C-PCA has excellent structural robustness and reusability, making it a very valuable material in oil absorption applications.

[0105] Aerogel oil absorption performance analysis experiment

[0106] Take 0.3g of PDMS@C-PCA aerogel material and test the oil absorption rate of three oils (petroleum, motor oil, rapeseed oil). Pour 20ml of oil into a beaker, put the weighed PDMS@C-PCA (M0=0.5g) flatly into the oil and let it stand for 10 minutes. Take out the aerogel from the beaker, place it flat on a metal filter for 5 minutes, weigh the mass of the aerogel after standing (M1), calculate the average oil absorption rate, test each oil 10 times, and take the average oil absorption to calculate the oil absorption rate C. The calculation formula of the oil absorption rate C is as follows:

[0107]

[0108] The calculated oil absorption test results of PDMS@C-PCA aerogel for three oils (petroleum oil, motor oil, and rapeseed oil) are shown in Table 6.

[0109] Table 6

[0110] Oil Type <![CDATA[Mass M0 of aerogel oil absorbent / g]]> <![CDATA[Average oil absorption M1 / g]]> Oil absorption rate / (g / g) Rapeseed Oil 0.30 8.125 27.30 Engine Oil 0.30 7.580 25.27 oil 0.30 9.337 30.13

[0111] As shown in Table 6, PDMS@C-PCA has a good adsorption effect on the three oils, and the maximum adsorption rates of rapeseed oil, motor oil and petroleum can reach 27.3g / g, 25.27g / g and 30.13g / g respectively. Obviously, the modified aerogel has the best adsorption effect on petroleum, and the oil absorption rate can reach more than 30 times. The good adsorption performance of PDMS@C-PCA on the three oils is mainly due to the presence of pores inside the aerogel, which has an adsorption effect, and the prepared material has more pores in the three-dimensional space, a large specific surface area, and thus a strong adsorption capacity.

[0112] Further, the oil absorption rate of PDMS@C-PCA aerogel material for three kinds of oil (petroleum, motor oil, rapeseed oil) was tested. An appropriate amount of oil was poured into a beaker and PDMS@C-PCA aerogel material was added. 1S, 2S, 3S, 4S, 5S, 10S, 15S, 20S, 30S, 40S, 50S, 60S, 90S, and 120S were taken as time points. The oil absorption rate of PDMS@C-PCA at these time points was tested. The above experimental operations were repeated in sequence and the experimental data were recorded. A curve with time as the horizontal axis and the oil absorption rate as the vertical axis was drawn. The straight line part of the curve was taken to calculate the oil absorption rate. The calculation formula of the oil absorption rate v is shown in Formula 2:

[0113]

[0114] In formula 2, v represents the average oil absorption rate, in g / (g / min); C max Indicates the adsorption amount at saturation, in g; t max It indicates the time for adsorption to reach saturation, in min.

[0115] The calculated adsorption rates of PDMS@C-PCA for the three oils at room temperature are as follows: Figure 5 As shown, a is the oil absorption ratio of PDMS@C-PCA within 120S. Figure 5 It can be seen that the oil absorption process of PDMS@C-PCA is divided into two stages: rapid adsorption process and adsorption equilibrium stage.

[0116] like Figure 5As shown in the figure, PDMS@C-PCA has good adsorption for the three oils. The oil absorption of rapeseed oil and motor oil is basically stable at about 10S, with oil absorption ratios of 26.3g / g and 24.7g / g, respectively. The oil absorption ratio of petroleum oil tends to be balanced at about 20S. After 1min, the oil absorption basically does not change and reaches saturation. As the adsorption time is further extended, the oil absorption of rapeseed oil and motor oil does not increase significantly, which also shows that the interaction between the adsorbent and the oil is mainly physical adsorption at porous points in the initial stage.

[0117] Photothermal performance analysis experiment of aerogel

[0118] According to the device shown in the figure below, the photothermal conversion test was carried out, where the surface facing the simulated solar light source was defined as the top surface, and the surface facing away from the simulated solar light source was defined as the bottom surface. Figure 6 As shown, a cold xenon lamp was used to simulate sunlight conditions (1000W / m 2 ), with a distance of one sun (10 cm), and an infrared camera was used to record the temperature change and the actual temperature of the sample, and to analyze the heating rate and thermal conductivity, and to evaluate the photothermal conversion effect of the material.

[0119] The timing starts from the moment the simulated sunlight source is turned on, and the temperature-time curves of the top and bottom surfaces are measured using an infrared camera. The heating rate of the top surface and the thermal conductivity of the material are calculated. The heating rate V is calculated as shown in Formula 3:

[0120]

[0121] In formula 3, T t is the temperature of the center point of the top surface after irradiation for tS; T0 is the initial temperature of the center point of the bottom surface; t is the irradiation time of the simulated solar light source.

[0122] The thermal conductivity is calculated by the Fourier equation, as shown in Formula 4:

[0123]

[0124] In formula 4, Q (kW / m 2 ) represents the heat flux, that is, the power of the energy supply source; k represents the thermal conductivity of the material; ΔT (℃) represents the temperature difference between the top and bottom surfaces of the material; ΔX (m) represents the thickness of the material; ΔT / ΔX represents the temperature gradient of the sample under the irradiation of the light source.

[0125] The temperature-time curves of the top and bottom surfaces of C-PCA were measured by infrared camera and compared with PCA to explore the effect of C-NPs on the photothermal oil absorption performance. The temperature change diagram is shown in the figure below. Figure 7 As shown, Figure 7In (a), A1 is the temperature change curve of the top of C-PCA, A2 is the temperature change curve of the bottom of C-PCA, B1 is the temperature change curve of the top of PCA, and B2 is the temperature change curve of the bottom of PCA; Figure 7 In (b), C1 is the temperature change curve of the top of C-PCA under the periodic switching light source, and C2 is the temperature change curve of the bottom of C-PCA under the periodic switching light source.

[0126] The top temperature of C-PCA increased from 25°C to 95°C within 50S, and the temperature gradually reached equilibrium after 100S. The heating rate in the rapid heating stage was 1.4°C / S. Figure 7 In the heating stage (a), the heating rates of the top surfaces of PCA and C-PCA are both fast, and the maximum temperatures are not much different, but the bottom surface temperatures are quite different. This is mainly because the good thermal conductivity of C-NPs in C-PCA allows the heat on the top surface to be quickly transferred to the bottom, causing the bottom surface temperature to rise significantly. Moreover, from the comparison in (b), it can be seen that when there is simulated sunlight, the top and bottom temperatures of C-PCA rise rapidly; when the light source is turned off, the upper and lower surface temperatures drop sharply, which shows that the temperature rise of the bottom surface of C-PCA comes from the heat conduction effect after the top surface is heated, and the heat conduction is rapid. In addition, C-PCA heats up to 99.8℃ in 120S and remains stable after multiple times. The bottom surface has the same trend, heating up to 47.8℃ and remaining stable. The surface material has excellent photothermal stability. Therefore, due to the addition of C-NPs, the thermal conductivity is greatly improved, making the C-PCA material have efficient photothermal conversion performance, which is sufficient to meet the practical application of photothermal oil absorption.

[0127] also, Figure 7 (a) It can be seen that the overall trend of the heating curves of PCA without C-NPs and C-PCA is similar, and the top temperature rise value is slightly lower, while the bottom surface is quite different. This is because the vegetable tanning agent used in the preparation of vegetable tanned animal leather contains a large amount of plant glue (plant adhesive), the main component of which is tannin. The hydrolyzed acid in tannin contains a large amount of π-π conjugated bonds, which cause the mutual influence of electron clouds, absorb solar energy and vibrate, and generate heat energy through the optical transition of π-π bonds. This is the natural characteristic of vegetable tanned leather. Therefore, PCA has self-heating properties under light, and the reason why the bottom temperature of PCA is low is that the thermal conductivity is insufficient, which is poorer than that of C-NPs. This also proves that C-PCA material has good thermal conductivity.

[0128] Ultrasonic stability analysis experiment of aerogel

[0129] 0.2g of PDMS@C-PCA loaded with nanoparticles was put into 100ml of simulated seawater and ultrasonicated in an ultrasonic cleaning machine for 10min, 20min, 40min, and 60min respectively. After the ultrasonication, the water was observed to see whether there were suspended nanoparticles to determine the adhesion strength of C-NPs nanoparticles in PDMS@C-PCA. The schematic diagram of the solution change after ultrasonication is shown in the figure. Figure 8 shown.

[0130] pass Figure 8 It can be seen that after 10 min, 30 min, and 60 min of ultrasound, the solution is still clear and there is no suspended C-NPs, which proves that PDMS@C-PCA has good ultrasonic stability.

[0131] In summary, the present invention provides a protein fiber-based composite aerogel material and a preparation method thereof, the preparation method comprising: adding vegetable tanned leather fiber to a dimethyl sulfoxide solvent, and keeping warm at 80°C for 30 minutes until the fiber is completely dissolved to obtain a vegetable tanned leather fiber / dimethyl sulfoxide solution; adding chitosan powder to distilled water, and then slowly dripping glacial acetic acid until the chitosan powder is completely dissolved to obtain a first mixed solution, and then adjusting the pH of the first mixed solution to 4 to obtain a chitosan solution; mixing the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in a volume ratio of 1-2:1-2:1-2, stirring and adding C-NPs and dispersing them evenly to obtain a second mixed solution, and then dispensing the second mixed solution into each porous plate, adding glutaraldehyde solution to the second mixed solution in each porous plate, stirring well and sealing, and placing the mixture in an environment of 60°C. The composite wet gel semi-finished product is obtained by heat preservation for 4 hours, and the mass of C-NPs is 0.15% of the mass of vegetable tanned leather fiber; the composite wet gel semi-finished product is taken out from each porous plate and placed at room temperature for 12-36 hours, and then the composite wet gel semi-finished product is soaked in anhydrous ethanol for 12-36 hours and then taken out, and then the composite wet gel semi-finished product is soaked in ultrapure water for 12-36 hours to obtain a carbon nano-protein-based composite wet gel material; the carbon nano-protein-based composite wet gel material is placed in a -60°C environment for freeze molding, and then sent to a vacuum freeze dryer for freeze drying to obtain a carbon nano-protein-based composite aerogel; the carbon nano-protein-based composite aerogel is soaked and modified with a PDMS hydrophobic agent solution for 2 hours, and then placed in a 120°C environment for drying for 20 minutes to obtain a protein fiber-based composite aerogel material. The present invention utilizes the photothermal conversion performance of tannin in the vegetable tanned leather fiber component to reduce the amount of photothermal conversion particles used in the preparation process of aerogel materials, thereby improving the photothermal conversion performance of the aerogel material while avoiding the problem of three-dimensional structure damage caused by excessive use of photothermal conversion particles, thereby improving the efficient and stable adsorption performance of the aerogel material for high-viscosity oil stains.

[0132] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that modifications or improvements can be made based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

[0133] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention herein. The present invention is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. It should be understood that the present invention is not limited to the precise structure that has been described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from the scope thereof.

Claims

1. A method for preparing a protein fiber-based composite aerogel material, characterized in that: The preparation method comprises: S10: adding the vegetable tanned leather fiber to the dimethyl sulfoxide solvent, and keeping the mixture in an environment of 80° C. for 30 minutes until the fiber is completely dissolved, thereby obtaining a vegetable tanned leather fiber / dimethyl sulfoxide solution, wherein the content of the vegetable tanned leather fiber in the vegetable tanned leather fiber / dimethyl sulfoxide solution is 5 g / 100 ml; S20: After adding chitosan powder to distilled water, continue to slowly drop glacial acetic acid until the chitosan powder is completely dissolved to obtain a first mixed solution, and then adjust the pH of the first mixed solution to 4 to obtain a chitosan solution, wherein the content of the chitosan powder in the chitosan solution is 4 g / 100 ml, and the volume ratio of the glacial acetic acid to the distilled water is 1:1; S30: mixing the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in a volume ratio of 1-2:1-2:1-2, adding C-NPs with stirring and evenly dispersing to obtain a second mixed solution, and then dispensing the second mixed solution into each porous plate, adding glutaraldehyde solution to the second mixed solution in each porous plate, stirring and sealing, and keeping warm at 60° C. for 4 hours to obtain a composite wet gel semi-finished product, wherein the mass of the C-NPs is 0.15% of the mass of the vegetable tanned leather fiber; S40: taking out the composite wet gel semi-finished product from each porous plate and placing it at room temperature for 12-36 hours, soaking the composite wet gel semi-finished product in anhydrous ethanol for 12-36 hours, taking it out, and then soaking the composite wet gel semi-finished product in ultrapure water for another 12-36 hours to obtain a carbon nano-protein-based composite wet gel material; S50: placing the carbon nano-protein-based composite wet gel material in a -60°C environment for freeze-forming, and then sending it into a vacuum freeze dryer for freeze-drying to obtain a carbon nano-protein-based composite aerogel; S60: After the carbon nano-protein-based composite aerogel is immersed in a PDMS hydrophobic agent solution for modification for 2 hours, it is placed in a 120° C. environment for drying for 20 minutes to obtain a protein fiber-based composite aerogel material.

2. The preparation method according to claim 1, characterized in that: The volume ratio of the vegetable tanned leather fiber / dimethyl sulfoxide solution, the chitosan solution and distilled water in S30 is 2:2:

4.

3. The preparation method according to claim 1, characterized in that: The content of glutaraldehyde in the glutaraldehyde solution is 2.5%, and the volume ratio of the glutaraldehyde solution to the vegetable tanned leather fiber / dimethyl sulfoxide solution in each porous plate is 3:

50.

4. The preparation method according to claim 1, characterized in that: The composite wet gel semi-finished product is left standing at room temperature for 24 hours, immersed in anhydrous ethanol for 12 hours, and immersed in ultrapure water for 12 hours.

5. The preparation method according to claim 1, characterized in that: The content of PDMS in the PDMS hydrophobic agent solution is 1.5%.

6. The preparation method according to claim 1, characterized in that: The preparation method of the vegetable tanned leather fiber comprises: The vegetable tanned leather scraps were cut into 2 cm × 3 cm sizes and then put into a grinder for grinding for 5 min to obtain the vegetable tanned leather fiber raw materials; The vegetable tanned leather fiber raw material is soaked in anhydrous ethanol for 2-4 days to wash out alcohol-soluble impurities, and then filtered and dried at 120° C. for 2 hours, and finally sent to a grinder for grinding for 5 minutes to obtain the vegetable tanned leather fiber.

7. The preparation method according to claim 1, characterized in that: The protein fiber-based composite aerogel material is applied to petroleum adsorption operations.

8. A protein fiber-based composite aerogel material, characterized in that: The protein fiber-based composite aerogel material is prepared by the method for preparing the protein fiber-based composite aerogel material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of oil adsorption material with hierarchical porous structure

    CN107857893A

  • Composite aerogel photocatalytic material and preparation method thereof

    CN110918130A

  • Preparation method and application of super-hydrophobic aerogel with both ultrafast oil adsorption capacity and high compression recovery performance

    CN115282888A